The Atlantic salmon interleukin 4/13 receptor family: Structure, tissue distribution and modulation of gene expression. Issue 98 (March 2020) - Sequeida, Alvaro; Castillo, Andrés; Cordero, Natalia; Wong, Valentina; Montero, Ruth; Vergara, Claudio; Valenzuela, Beatriz; Vargas, Deborah; Valdés, Natalia; Morales, Jonathan; Tello, Mario; Sandino, Ana María; et al.
Abstract: Interleukin (IL)-4 and IL-13 play a central role in T helper 2 immune response in mammals. The cell signalling is mediated by the type I heterodimeric receptor containing the IL-4Rα and γC chains, and the type II receptors formed by IL-4Rα and IL-13Rα1. In salmonid species, three paralogues of the IL-4 and IL-13 cytokines have been reported, il-4/13a, il-4/13b1 and il-4/13b2. In regard to receptors, two paralogues of each IL-4/13 receptor chains have been identified in rainbow trout while five genes named γc1, il-4rα, il-13rα1a, il-13rα1b, and il-13rα2 have identified in Atlantic salmon. Since Atlantic salmon is an important farmed fish species, the aim of this work was to get new insights into distribution, structure and expression regulation of the IL-4/13 receptors in salmon. By using qRT-PCR, it was shown that all γc1, il-4rα, il-13rα1a, il-13rα1b, and il-13rα2 receptor chains were expressed in lymphoid and non-lymphoid tissues of healthy salmon, nonetheless γC expression was higher in lymphoid than non-lymphoid tissues. The in silico structural analysis and homology modelling of the predicted receptor proteins showed that domains and most motifs present in the superior vertebrate chains are conserved in salmon suggesting a conserved role for these receptor chains. Only IL-13Rα1B is a receptor chain with a unique structure that seem not to be present in higher vertebrates but in fish species. In order to determine the regulatory role of IL-4/13 on the expression of receptor chains, Atlantic salmon il-4/13A gene was synthetized and cloned in pET15b. The recombinant IL-4/13A was produced in E. coli and the activity of the purified cytokine was confirmed in vitro . The regulatory role of IL-4/13A on the expression of their potential receptors was tested in salmon receiving the recombinant cytokine and effects were compared with those of the control group. The results showed that IL-4/13A induced the expression of its own gene and GATA-3, in the head kidney of fish but not in the spleen, while IL-10 increased in both lymphoid organs indicating a regulatory role of this cytokine on the induction of Th2 responses in salmon. IFN-γ and MHC class II were also later induced in head kidney. In regard to the expression of the receptor chains, IL-4/13A upregulated the expression of γC, IL-13Rα1A and IL-13Rα2A in the spleen but not in the head kidney of salmon, indicating a role on the modulation of cell signalling for the Th2 response. Furthermore, Piscirickettsia salmonis infection of Atlantic salmon occurred with an increase of γC and IL-13Rα1A suggesting a potential role of the IL-4/13 system in bacterial immunity or pathogenesis. This study contributes to a better understanding of the IL-4/13A system in salmon, which as a key axis for Th2 response may be involved not only in pathogen elimination but also in adaptive immune repair that seems critical tolerance to infectious diseases. Highlights: Five IL-4/13 receptor genes of Atlantic salmon are expressed in lymphoid and non-lymphoid tissues. The protein structure of salmon receptor chains showed conserved domains and motifs. IL-4/13A induces the expression of γC, IL-13Rα1A and IL-13Rα2A in the spleen of salmon. Expression of γC and IL-13Rα1A increase in head kidney during P. salmonis infection of Atlantic salmon.